Legal Protection of Remote Working Workers in Particular Time Employment Agreements - Arsyi Manggali Arya Putra; Mohammad Isrok; Nur Putri Hidayah (Audito Comparative Law Journal (ACLJ), 2023)
In the Industrial Era 4.0, all electronic work systems can support the concept of remote working. The relationship between workers and companies arises from a work agreement. The fact is that work agreements are inseparable from conflicts, especially in Particular Time Employment Agreements. Remote working workers in a Particular Time Employment Agreement are carried out online, which must comply with the applicable laws and regulations. This study uses a normative legal method by analyzing and comparing the norms of the Indonesian state legislation (statute approach) descriptively, namely the updated Labor Law, the Job Creation Law, and the ITE Law. And take a conceptual approach, namely remote working (conceptual approach). Furthermore, the researcher describes the formulation of the problem, namely the Remote Working Concept with a Particular Time Employment Agreement system. The Remote Working Concept of Worker Protection is reviewed in the Job Creation Law. In principle, the mechanism for implementing the remote working concept is subject to the provisions of the Labor Law and the Job Creation Law. In addition, there is a need for a new clause regarding the concept of remote working to protect remote working concept workers fairly.